The UTAUT Model on Decision to Use Amaan Islamic Fintech Financing: Prior Experience as Moderating - Dini Ayu Puspita Sari; Meliana, Rini; Amanah Aida Qur'an; Azka Nur Diana (Faculty of Islamic Economics and Business, UIN Prof. K. H. Saifuddin Zuhri Purwokerto, 2025)
Entering the digital era, industry players are increasingly aggressively developing digital technology. One of the technological developments that has become the subject of recent studies in Indonesia is financial technology (fintech). There are women micro- entrepreneurs who need support in development, especially capital support to improve their businesses. PT Amaan Indonesia Sejahtera (Amaan) is an integrated solution that can be accessed by women micro-entrepreneurs in the form of financial or business capital financing. Because Amaan is one of the digital-based microfinance services with an easier mechanism and has a clear commitment to empowering women in the business sector. The study aims to test the UTAUT model with moderated prior experience. This research uses a quantitative approach. The data used is a questionnaire distributed to 250 respondents via google form. The data analysis method uses descriptive statistical analysis, multiple regression analysis and moderated regression analysis (MRA) using the SmartPLS (v3.0) analysis tool. The results show that performance expectancy, effort expectancy, social influence and facilitating conditions have a significant effect on the decision to use Amaan Islamic fintech financing. Prior experience as a moderating variable weakens the effect of performance expectancy and effort expectancy. Meanwhile, prior experience strengthens the influence of social influence and facilitating conditions on the decision to use Amaan Islamic fintech financing. RSquare shows that the user decision variable has a value of 0.539. This means that the ability of variable X to explain Y is 53.9% (medium), so it is said that the ability of the user decision variable to be influenced by the variables of performance expectancy, effort expectancy, social influence, facilitating conditions and prior experience is quite strong. While the remaining 46.1% is influenced by other variables outside the study.